The XMM-Newton survey of the Small Magellanic Cloud: XMMU J010633.1-731543 and XMMU J010743.1-715953, two new Be/X-ray binary systems★ - Coe, M. J.; Haberl, F.; Sturm, R.; Bartlett, E. S.; Hatzidimitriou, D.; Townsend, L. J.; Udalski, A.; Mereghetti, S.; Filipović, M. (2012)
In the course of the XMM-Newton survey of the Small Magellanic Cloud (SMC), two new bright X-ray sources were discovered exhibiting the spectral characteristics of high-mass X-ray binaries - but revealing only weak evidence for pulsations in just one of the objects (at 153 s in XMMU J010743.1-715953). The accurate X-ray source locations permit the identification of these X-ray sources with Be stars, thereby strongly suggesting that these systems are new Be/X-ray binaries. From blue spectra the proposed classification for XMMU J010633.1-731543 is B0.5-1Ve and for XMMU J010743.1-715953 it is B2IV-Ve.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; stars: neutron; X-rays: binaries